Lattice gas with nearest-neighbor exclusion in a shear-like field - Potiguar,Fabricio Q. (2006)
We present Monte Carlo simulations of the lattice gas with nearest-neighbor exclusion and Kawasaki (hopping) dynamics (hard square lattice gas), under the influence of a nonuniform drive, on the square lattice. The drive, which favors motion along the +x axis and inhibits motion in the opposite direction, varies linearly in the y direction. Our lattice has rigid walls at the end points in the y direction and periodic boundaries along the drive. We find that this model has transition to a sublattice-ordered phase at a density of about 0.298, lower than in equilibrium (rhoc @ 0.37), but somewhat higher than in the uniformly driven case at maximal bias (rhoc @ 0.272). For smaller global densities (r < 0.33), the ordering occurs with particle accumulation in the low-drive region. Above this density we observe a surprising reversal in the density profile, with particles migrating to the high-drive region.